Beyond the Shades of Darkness: A Case Study of Varanasi, India - SHARMA, Nitasha (Téoros)

(untitled) (Université du Québec à Montréal, 2016)
Dark tourism scholarship, so far, has mostly confined itself to European interpretations of rituals and death. This study aims at analyzing the phenomenon of dark tourism in the context of a non-Western and religious setting in India focusing specifically on tourist interest and perceptions. The study focuses upon two types of Hindu death-related rituals performed at the cremation grounds and attempts to understand how travelling to religious sites and witnessing “live” events of death can fall under the broad context of dark tourism, and how the different meanings associated by tourists form paradoxes and ambiguities that existing dark tourism scholarship fails to address adequately.